Rapid determination of histamine concentration in fish (Miichthys Miiuy) by surface-enhanced Raman spectroscopy and density functional theory - Bingquan, Chu; Lei, Lin; Yong, He (International Journal of Agricultural and Biological Engineering, 2017)
Histamine is a type of biogenic amine, which plays a major role in the health problems associated with seafood consumption. Legislative limits of histamine level in seafood have been set in many countries. This study focuses on investigating the feasibility and potentiality of determining histamine concentration in fish (Miichthys miiuy) by surface-enhanced Raman spectroscopy (SERS) combined with density functional theory (DFT). Both a gold colloid and a silver colloid were used to determine the enhancement effect for SERS detection of histamine standard solution, and the gold colloid exhibited more effective as compared to the silver colloid. The protocol on extraction of histamine with 12% trichloroacetic acid and adjustment of pH with NaOH solution (5 mol/L) could significantly shorten sample preparation (20 min) and provide clear SERS spectra of histamine. The peaks of histamine molecules were classified using the DFT and five spectra (953 cm-1, 992 cm-1, 1106 cm-1, 1262 cm-1 and 1317 cm-1) were selected as the characteristic bands of histamine discrimination. Moreover, the intensity of the peak at 1262 cm-1 had a good linear relationship with histamine concentration at 5-400 mg/kg with R2=0.9755. It is concluded that the SERS-DFT approach will be a potential method for rapidly and reliably detecting histamine at levels from 5 mg/kg to 400 mg/kg in fresh fish. Keywords: surface-enhanced Raman spectroscopy (SERS), density functional theory (DFT), gold nanoparticles, histamine, rapid determination, fish (Miichthys miiuy), food safety DOI: 10.25165/j.ijabe.20171004.3468 Citation: Chu B Q, Lin L, He Y. Rapid determination of histamine concentration in fish (Miichthys Miiuy) by surface-enhanced Raman spectroscopy and density functional theory. Int J Agric & Biol Eng, 2017; 10(4): 252–258.